From challenges to coping strategies: A study on academic integration and psychological well-being among international students at Chinese universities - Mahmood, Rabia; Ahmed, Waqas; Mahmood, Sadaf; Suleman, Rao Muhammad Faisal; Shabbir, Muhammad; Wang, Freda Yangrong (Journal of International Students, 2026)
International students in China face interrelated cultural, academic, and psychological challenges that shape their adaptation and well-being. This study explored these difficulties and the coping strategies that students employ in Chinese higher education. Drawing on Berry’s acculturation theory and Lazarus and Folkman’s coping theory, semi-structured interviews were conducted with 30 international students across six locations. Thematic analysis identified key obstacles, including language barriers, unfamiliar pedagogies, delayed stipends, high academic demands, and perceived discrimination. These factors contribute to acculturative stress, homesickness, social isolation, and depressive symptoms. Students nonetheless demonstrated resilience through emotion-focused coping, such as peer support, virtual family contact, and religious or cultural practices, and problem-focused strategies, including structured study habits, institutional navigation, and language improvement. The findings show that institutional limitations, particularly inadequate mental health services and weak language support, can heighten psychological distress.